"Dempathy" ‐ From empathy to synchronization in understanding people with dementia: Developing topics. (7th December 2020) - Chui, Kenny Chi Man
Abstract: Background: In Hong Kong, dementia is one of the significant reasons for the family caregivers to send their beloved one to the residential care homes. Nevertheless, over 50% of current residents are in cognitive impairment and different stages of dementia. The caring staff face a lot of challenges and uncertainty, even worries and anxiety in taking care of people with dementia. How to facilitate the care staff to implement person‐centred care is what we all would like to find out. The research began two reflective training sessions, each of which lasted 90 minutes with over 25 frontline care staff, by presenting some of the subjective experiences of residents with dementia with the aim of arousing empathy for their self‐perceptions. Afterwards, I asked the attendees a series of reflective questions as prompts to promote their reconsideration of how people with dementia might be cared for by following the person‐centred approach. The same semi‐structured questions were designed for both focus groups to gain insight into the staff's thoughts about the self‐perception of people with dementia and the reflective training. The participating care staff had reflected upon their attitudes, skills and knowledge related to dementia care. Hardly any care staff reported having ever thought about the self‐perception or subjective views of people with dementia. On the contrary, they had assumed that people with dementia were incapable of giving rational responses and that it was therefore unnecessary to listen to their points of view. Themes including (1) From Stigmatization to Acceptance; (2) From Perceiving the Patient to Perceiving the Person; (3) From Ignoring to Responding; (4) From Being Tasked‐Oriented to Being Relationship‐Oriented; (5) From Denying to Recognizing People with Dementia were found. In the focus groups, however, the care staff suggested that they had become aware of ways to understand people with dementia from their perspectives and in their context. The implementation of person‐centred approach is associated with the change of caring attitude and perception of dementia at the fundamental level. The reflective training facilitated the care staff to transform from empathy to synchronization towards the context of people with dementia, which I called "Dempathy".